Evaluation of Weight Gain in Piglets during Lactation in Technical and Traditional Farrowing Rooms - García-Aguirre, María Johana; Villa-Ramírez, Rigoberto; Hurtado-Villegas, Jaime (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The objective of this work was to evaluate the weight gain in piglets during lactation in technified and traditional farrowing rooms. This research was carried out in the facilities of the Bengal Experimental Farm of the University of Quindío, located in the municipality of Filandia at 2,050 meters of altitude, where the weight gains of 53 piglets of landrace sows were evaluated, which were housed in traditional and technified farrowing rooms with previously disinfected heating plates. During the weaning stage (21 days), the handling for both treatments was similar, which implied manipulating the temperature inside the farrowing’s to maintain the body heat of the swine neonates. The weights were recorded from birth to the end of the stage of weaning; a completely random design was used. The analysis of variance showed that no P-value is less than 0.05; therefore, none of the factors has a statistically significant effect on weight with a 95.0 % confidence level. The general average from birth to weaning (21 days) in technified farrowing rooms is 6400 g/piglet, which indicates that the weekly increase of piglets in technified cages is at an average of 1300 g; while piglets born in non-technified or traditional farrowing rooms earn an average of 1200 g per week.